Validation and reproducibility of dietary assessment methods in adolescents: a systematic literature review. Issue 12 (18th November 2013) - Tabacchi, Garden; Amodio, Emanuele; Di Pasquale, Maria; Bianco, Antonino; Jemni, Monèm; Mammina, Caterina
Abstract Objective The aim of the present work was to determine what dietary assessment method can provide a valid and accurate estimate of nutrient intake by comparison with the gold standard. Design A MEDLINE, EMBASE, ISI Web of Science, Cochrane and related references literature review was conducted on dietary assessment methods for adolescents reporting the validity and/or reproducibility values. A study quality assessment on the retrieved FFQ was carried out according to two different scoring systems, judging respectively the quality of FFQ nutrition information and of FFQ validation and calibration. Setting The present review considered adolescents attending high schools and recruited in hospitals or at home. Subjects The target of the review was the healthy adolescent population in the age range 13–17 years. Results Thirty-two eligible papers were included and analysed separately as 'original articles' (n 20) and 'reviews' (n 12). The majority (n 17) assessed the validation and reproducibility of FFQ. Almost all studies found the questionnaires to be valid and reproducible (r > 0·4), except for some food groups and nutrients. Different design and validation issues were highlighted, such as portion-size estimation, number of food items and statistics used. Conclusions The present review offers new insights in relation to the characteristics of assessment methods for dietary intake in adolescents. Further meta-analysis is required although the current review provides important indications on the development of a new FFQ, addressing the need for a valid, reproducible, user-friendly, cost-effective method of accurately assessing nutrient intakes in adolescents.